Dlaczego powstają nowe przekłady? Mistrz i Małgorzata Michaiła Bułhakowa w nowym tłumaczeniu na język polski - Mocarz-Kleindienst, Maria (Przekłady Literatur Słowiańskich, 2018)
Why Do New Translations Come into Being? Mikhail Bulgakov’s The Master and Margarita in a New Polish Translation Literary works tend to be amongst the most often translated texts. A perfect example is Mikhail Bulgakov’s novel The Master and Margarita: over the previous two years (2016—2017) three new translations thereof into Polish appeared, one of them being a translation by Leokadia, Grzegorz, and Igor Przebinda. In this paper, the main reasons for the publication of this new, “family” translation were discussed. The question about the need for makeing new translations was accompanied by other questions: how are such texts translated what strategies are used by the translator?, to what extent does he or she take account of the assumed expectations of contemporary readers? In the presentation, two research perspectives were proposed. The first of them is the translator’s viewpoint, for whom the newly done translation is a domesticated translation. The other perspective, the researcher’s one, consist in analyzing the translated text itself, in particular with regard to the applied translation strategies (exoticization vs. adaptation), indicating the differences between the latest translation and the previous ones (first by Irena Lewandowska and Witold Dąbrowski, and second by Andrzej Drawicz). The analysis of the translated text along with the accompanying paratexts in the form of numerous footnotes leads one to a conclusion that exoticization is a dominant strategy. KEY WORDS: domestication, exoticization, Master and Margarita, Mikhail Bulgakov